LOCUL DE MUNCĂ – BIBLIOTECA MUNICIPALĂ. GRADUL DE IDENTIFICARE CU INSTITUŢIA - BUTUCEL, Magistru, Elena; KULIKOVSKI, conf. univ. , Lidia (BIBLIOPOLIS, 2020)
An efficient management suppose taking into account all objective and subjective moments which conduct to the performances at the workplaces. Now, the management of the workplace became for the libraries an important process, a concept, a strategy, essential for the surviving and development. In order to underline the importance of the workplaces in the information institution which conduct to the necessity of a study about the evaluation of the effi ciency of the workplaces in the libraries (on the example of the Municipal Library B.P. Hasdeu). In the article is commented, analyzed only two questions: open questions related to the workplaces images. The survey was applied for 107 respondents, employees of the Municipal Library. The answers linking to posts studies, age, length of service permitted to conclude that more than half of respondents identify their job with the Municipal Library. The conclusion can serve as a support for libraries in their eff orts to build performing team.